New specific HSP47 functions in collagen subfamily chaperoning. Issue 9 (27th July 2020) - Köhler, Anna; Mörgelin, Matthias; Gebauer, Jan M.; Öcal, Sinan; Imhof, Thomas; Koch, Manuel; Nagata, Kazuhiro; Paulsson, Mats; Aumailley, Monique; Baumann, Ulrich; Zaucke, Frank; Sengle, Gerhard
Abstract: Although collagens are the most abundant proteins implicated in various disease pathways, essential mechanisms required for their proper folding and assembly are poorly understood. Heat‐shock protein 47 (HSP47), an ER‐resident chaperone, was mainly reported to fulfill key functions in folding and secretion of fibrillar collagens by stabilizing pro‐collagen triple‐helices. In this study, we demonstrate unique functions of HSP47 for different collagen subfamilies. Our results show that HSP47 binds to the N‐terminal region of procollagen I and is essential for its secretion. However, HSP47 ablation does not majorly impact collagen VI secretion, but its lateral assembly. Moreover, specific ablation of Hsp47 in murine keratinocytes revealed a new role for the transmembrane collagen XVII triple‐helix formation. Incompletely folded collagen XVII C‐termini protruding from isolated HSP47 null keratinocyte membrane vesicles could be fully restored upon the application of recombinant HSP47. Thus, our study expands the current view regarding the client repertoire and function of HSP47, as well as emphasizes its importance for transmembrane collagen folding.